Trypanocidal and Anti-Inflammatory Effects of Three ent-Kaurane Diterpenoids from Gymnocoronis spilanthoides var. subcordata (Asteraceae) - Selener, Mariana Gabriela (2024)
Chagas disease, caused by the protozoan Trypanosoma cruzi, affects 6–7 million people worldwide. The dichloromethane extract obtained from the aerial parts of Gymnocoronis spilanthoides var subcordata showed trypanocidal activity in vitro. The fractionation of the dewaxed organic extract via column chromatography led to the isolation of three diterpenoids: ent-9α,11α-dihydroxy-15-oxo-kaur-16-en-19-oic acid or adenostemmoic acid B, (16R)-ent-11α-hydroxy-15-oxokauran-19-oic acid and ent-11α-hydroxy-15-oxo-kaur-16-en-19-oic acid. These compounds showed IC50 values of 10.6, 15.9 and 4.8 µM against T. cruzi epimastigotes, respectively. When tested against amastigotes, the diterpenoids afforded IC50 values of 6.1, 19.5 and 60.6 µM, respectively. The cytotoxicity of the compounds was tested on mammalian cells using an MTT assay, resulting in CC50s of 321.8, 23.3 and 14.8 µM, respectively. The effect of adenostemmoic acid B on T. cruzi was examined at the ultrastructural level using transmission microscopy. Treatment with 20 μM for 48 h stimulated the formation of abnormal cytosolic membranous structures in the parasite. This compound also showed an anti-inflammatory effect in murine macrophages stimulated with LPS and other TLR agonists. Treatment of macrophages with adenostemmoic acid B was able to reduce TNF secretion and nitric oxide production, while increasing IL-10 production. The combination of adenostemmoic acid B with benznidazole resulted in greater inhibition of NF-kB and a decrease in nitrite concentration. The administration of adenostemmoic acid B to mice infected with trypomastigotes of T. cruzi at the dose of 1 mg/kg/day for five days produced a significant decrease in parasitemia levels and weight loss. Treatment with the association with benznidazole increased the survival time of the animals. In view of these results, adenostemmoic acid B could be considered a promising candidate for further studies in the search for new treatments for Chagas disease.